The law's universal condemning and enslaving power: reading Paul, the Old Testament, and Second Temple Jewish literature - Blazosky, Bryan (Bulletin for Biblical Research Supplement, 2019)
cover FRONT -- Copyright Page -- Table of Contents -- Acknowledgments -- Introduction -- Chapter 1: The Torah -- Chapter 2: The Prophets and the Writings -- Chapter 3: The Second Temple Jewish Literature -- Chapter 4: Galatians -- Chapter 5: Romans -- Chapter 6: 1 Corinthians and the Disputed Pauline Epistles -- Conclusion -- Bibliography -- Index of Authors -- Index of Scripture -- Bulletin for Biblical Research Supplements.